The centrosome : Cell and molecular mechanisms of functions and dysfunctions in disease - Schatten, Heide (Humana Press, 2012)
This book features a diversity of aspects on centrosome biology focused on the role of centrosomes in reproduction, cell and molecular biology of centrosomes, centrosome abnormalities in cancer, and centrosomes in various cell systems. Each section contains a variety of different subtopics written by experts in their respective fields who have contributed significant new knowledge to decipher structure and the multiple functions of this still intriguing central organelle. The chapters include comprehensive and concise reviews of key topics in the field as well as cell and molecular details that are important for the specific subtopics. Cutting edge new information is balanced with background information that is readily understandable for the newcomer and the experienced centrosome researcher alike. In addition, several articles will raise awareness of centrosomes in areas that have not yet considered centrosomes associated with disease including aspects of misguided signal transduction and several others that may find centrosomes as new targets for therapeutic intervention. The topics addressed are selected to be of interest to scientists, students, teachers, and to all who are interested in expanding their knowledge related to centrosomes. The book is intended for a large audience as a reference book on the subject.